2004
DOI: 10.1128/aem.70.7.4088-4095.2004
|View full text |Cite
|
Sign up to set email alerts
|

Populations Implicated in Anaerobic Reductive Dechlorination of 1,2-Dichloropropane in Highly Enriched Bacterial Communities

Abstract: 1,2-Dichloropropane (1,2-D), a widespread groundwater contaminant, can be reductively dechlorinated to propene by anaerobic bacteria. To shed light on the populations involved in the detoxification process, a comprehensive 16S rRNA gene-based bacterial community analysis of two enrichment cultures derived from geographically distinct locations was performed. Analysis of terminal restriction fragments, amplicons obtained with dechlorinator-specific PCR primers, and enumeration with quantitative real-time PCR as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…Dehalococcoides-containing consortia included cultures SZ(PCE) and SZ(VC), which were derived from SuZi Creek sediment (Seoul area, South Korea), with PCE and VC as electron acceptors, respectively. Cultures KS(1,2-D) and RC(1,2-D), which do not utilize chloroethenes as electron acceptors, were derived from Alaska and Michigan river sediments, respectively, and were grown with 1,2-dichloropropane (1,2-D) (39). Bio-Dechlor INOCULUM (BDI), a commercially available PCE-to-ethene-dechlorinating consortium that has been used successfully for bioaugmentation at chloroethene-contaminated sites (40), was maintained in MM amended with lactate and TCE.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dehalococcoides-containing consortia included cultures SZ(PCE) and SZ(VC), which were derived from SuZi Creek sediment (Seoul area, South Korea), with PCE and VC as electron acceptors, respectively. Cultures KS(1,2-D) and RC(1,2-D), which do not utilize chloroethenes as electron acceptors, were derived from Alaska and Michigan river sediments, respectively, and were grown with 1,2-dichloropropane (1,2-D) (39). Bio-Dechlor INOCULUM (BDI), a commercially available PCE-to-ethene-dechlorinating consortium that has been used successfully for bioaugmentation at chloroethene-contaminated sites (40), was maintained in MM amended with lactate and TCE.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative information regarding the presence of Dehalococcoides organisms has been obtained using PCR primers that targeted signature regions of the 16S rRNA gene (18,29). Sensitivity was further improved using an initial amplification of community 16S rRNA genes with Bacteria-targeted primers, followed by PCR with Dehalococcoides-specific, internal primers (i.e., nested PCR), effectively increasing the detection limit by 2 orders of magnitude (29,39). After the significance of Dehalococcoides to chloroethene detoxification was realized, quantitative PCR methods to enumerate Dehalococcoides 16S rRNA gene copies were developed and applied (8,15,16,26,47).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Culture broth was centrifuged for 15 min at 8650g and supernatant was collected and examined for CHE activity based on Gallo's method 1 . Bacterial isolates producing CHE were identified by using PCR amplification of 16 S rDNA gene employing bacterial universal primers Bac8F (5 -AGAGTTTGATCCTGGCTCAG-3 ) and Bac1492R (5 -ACGGTTACCTTGTTACGACTT-3 ) 26 . Reaction mixtures were manipulated in 100 µl volumes containing 100 ng of DNA samples, 1 × PCR buffer, 20 µl of each primer, 10 mM dNTP, 1.5 mM MgCl 2 , and 1.5 units of Taq DNA polymerase.…”
Section: Bacterial Screening and Genetic Identificationmentioning
confidence: 99%
“…Analyzing the strain diversity of Dehalococcoides species is a challenging task because cell abundance is low and species are very closely related based on 16S rRNA gene sequence comparison. Recent studies have demonstrated that common phylogenetic markers, like the 16S rRNA gene, are not sufficient to distinguish between closely related Dehalococcoides strains exhibiting different dechlorinating activities (9,15,42,43). However, molecular probing of genes that encode enzymes catalyzing different dechlorination reactions provides the resolution to distinguish between Dehalococcoides strains with different metabolic abilities to grow with chlorinated ethenes as electron acceptor.…”
Section: Introductionmentioning
confidence: 99%